Bergson and the art of immanence : painting, photography, film - De Mille, Charlotte; De Mille, Charlotte; Ó Maoilearca, John; Ó Maoilearca, John (Edinburgh University Press, 2013)
8. Pasearse: Duration and the Act of Photographing9. Duration and Rhetorical Movement; 10. A Diagram of the Finite-Infinite Relation: Towards a Bergsonian Production of Subjectivity; Part III Immanence of the Visible; 11. Painting the Invisible: Time, Matter and the Image in Bergson and Michel Henry; 12. 'For We Will Have Shown it Nothing': Bergson as Non-Philosopher (of) Art; 13. The Untimeliness of Bergson's Metaphysics: Reading Diffractively; 14. Hyperaesthesia and the Virtual; Afterword: An Art Historical Return to Bergson; Index